Discussion of the Value and Implementation Strategy Brought by Frequency Re-Farming in China Mobile Industry - Dongzhao Zhu; Junxiao Shi; Yi Yu (Dianxin kexue, 2015)
The issues of investments on mobile network and its coverage affected by different wireless spectrum was studied, with the importance and desirability of frequency re-farming being analyzed systematically in reference to the current spectrum resource allocation and development status of mobile services in China. The value brought by frequency re-farming was explored from the perspective of cooperative networking and mobile network deployment, as the implementation strategy of frequency re-farming was proposed.